2016
DOI: 10.1111/jog.12946
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of very low birthweight, malformation, and low Apgar score among newborns inBrazilaccording to maternal urban or rural residence at birth

Abstract: Aim: Adverse birth outcomes are a major public health issue in rural areas, where several environmental risk factors, including pesticides, may endanger the health of women of reproductive age. We investigated the prevalence of selected birth outcomes among newborns from mothers living in urban and rural areas of a Brazilian municipality.Methods: Information about all live births that occurred between 2004 and 2006 in the Municipality of Nova Friburgo, Brazil, was retrieved from the Live Birth Information Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
4
15
2
5
Order By: Relevance
“…The following items were used to appraise cohort studies: [ 1 ] similarity of groups, [ 2 ] similarity of exposure measurement, [ 3 ] validity and reliability of measurement, [ 4 ] identification of confounder, [ 5 ] strategies to deal with confounder, [ 6 ] appropriateness of groups/participants at the start of the study, [ 7 ] validity and reliability of outcome measured, [ 8 ] sufficiency of follow-up time, [ 9 ] completeness of follow-up or descriptions of reason to loss to follow-up, [ 10 ] strategies to address incomplete follow-up, and [ 11 ] appropriateness of statistical analysis. The items used to appraise case-control studies were: [ 1 ] comparable groups, [ 2 ] appropriateness of cases and controls, [ 3 ] criteria to identify cases and controls, [ 4 ] standard measurement of exposure, [ 5 ] similarity in measurement of exposure for cases and controls, [ 6 ] handling of confounder [ 7 ], strategies to handle confounder, [ 8 ] standard assessment of outcome, [ 9 ] appropriateness of duration for exposure, and [ 10 ] appropriateness of statistical analysis. Studies got 50% and above of the quality scale were considered low risk.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following items were used to appraise cohort studies: [ 1 ] similarity of groups, [ 2 ] similarity of exposure measurement, [ 3 ] validity and reliability of measurement, [ 4 ] identification of confounder, [ 5 ] strategies to deal with confounder, [ 6 ] appropriateness of groups/participants at the start of the study, [ 7 ] validity and reliability of outcome measured, [ 8 ] sufficiency of follow-up time, [ 9 ] completeness of follow-up or descriptions of reason to loss to follow-up, [ 10 ] strategies to address incomplete follow-up, and [ 11 ] appropriateness of statistical analysis. The items used to appraise case-control studies were: [ 1 ] comparable groups, [ 2 ] appropriateness of cases and controls, [ 3 ] criteria to identify cases and controls, [ 4 ] standard measurement of exposure, [ 5 ] similarity in measurement of exposure for cases and controls, [ 6 ] handling of confounder [ 7 ], strategies to handle confounder, [ 8 ] standard assessment of outcome, [ 9 ] appropriateness of duration for exposure, and [ 10 ] appropriateness of statistical analysis. Studies got 50% and above of the quality scale were considered low risk.…”
Section: Methodsmentioning
confidence: 99%
“…Studies got 50% and above of the quality scale were considered low risk. The following items were used to appraise cross-sectional studies: [ 1 ] inclusion criteria, [ 2 ] description of study subject and setting, [ 3 ] valid and reliable measurement of exposure, [ 4 ] objective and standard criteria used, [ 5 ] identification of confounder, [ 6 ] strategies to handle confounder, [ 7 ] outcome measurement, and [ 8 ] appropriate statistical analysis. Studies were considered low risk when it scored 50% and above of the quality assessment indicators.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, epidemiologic studies examining the effects of pesticides on preterm birth and low birthweight have yielded inconsistent results. While ecological and cross-sectional studies have reported positive associations between preterm birth and low birthweight and pesticide use in agriculture [ 14 , 15 , 16 ], results from studies assessing self-reported or occupational use of pesticides have been inconsistent [ 17 , 18 , 19 ]. Nevertheless, small biomarker-based studies with measured organochlorines and/or organophosphates and their metabolic breakdown products in maternal blood, urine, or umbilical cord blood have suggested positive associations with preterm birth or with lower birthweight, with variation between the chemicals and outcomes assessed [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 25 studies of residential proximity to pesticide applications suggested weak or no effects on preterm birth and low birthweight, possibly due to misclassification in the exposure assessment [ 23 ]. Yet, more recent residential proximity studies using simple or area-level exposure assessments have provided some evidence that pesticides influence birth outcomes [ 16 , 24 , 25 ]. Three Geographic Information System (GIS)-based studies of the San Joaquin Valley of California (~1997–2011) reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%